Aktifitas Ekstrak Daun Mimba ( Azadiracltta Indica Juss) terhadap Jumlah Blastospora, Pseudohifa, Koloni Candida Albicans dan Sel Makrofag pada Kandidiasis Vaginalis (Penelitian Eksperimental Laboratoris pada Hewan Coba Rallus norvegicus) - Dwi Purwanti (2010)
The objective of this study was to prove the reduction of the number of blastopore, pseudohypha, and C. albicans colonies and the increase of macrophage count in vaginal candidiasis model of Rattus norvegicus receiving the extract of mimba leaf. There were five groups, divided into negative control group (K-) that was not inoculated with C. albicans and received no consumption of mimba leaf extract, positive control group (K +) that was inoculated with C. albicans and received fluconazol antifungal consumption of 0.035 mg/100 g BW, and treatment groups, P1 group inoculated with C. albicans and received mimba leaf extract in a dose of 19 mg/1 00 g BW, P2 group inoculated with C. albicans and received mimba leaf extract in a dose of 57 mg/100 g BW, and P3 group inoculated with C. albicans and received mimba leaf extract in a dose of95 mg/100 g BW. Treatment was given starting from day 7 up to day 28. Each group was observed on day 7 pre-treatment and on day 29 post-treatment by making swab to the rats' vagina for the counting of blastopore, pseudohypha, C. albicans colony, and macrophage. The result of paired T -test revealed that blastopore count had significant difference (p < 0.05) except inK- group (p > 0.05). The result of one-way Anova test indicated difference between groups (p < 0.05). LSD test revealed no difference between the groups K +, P 1, P2 and P3. Whereas, these groups had difference with Kgroup. The result of paired t-test on pseudohypha count showed significant difference (p < 0.05), except inK- group. The result of Brown Forsyte test (p > 0.05) showed no difference. The result of paired t-test on the number of C. albicans colonies showed difference (p < 0.05) except inK- group. The result of one-way Anova test (p < 0.05) indicated difference between groups. LSD test revealed no difference between the groups K+, P1, P2 and P3, while with K- group those groups had difference. The result of paired t-test on macrophage count showed significant difference (p < 0.05), except in K- group (p > 0.05). The result of Brown Forsythe test revealed difference (p < 0.05) between gorups. LSD test revealed difference between K- with P2 and P3, K +with P1 and P3. In conclusion, the extract of mimba leaf can reduce the number of blastopore, pseudohypha, and C. albicans colonies, and can increase macrophage count. It is suggested to perform studies on the compound contained within the ethanol extract of mimba leaf that has antifungal function, studies on experimental animals using more varied doses and sampling times, studies on mimba leaf as immunomodulator, and studies on its toxicity and side effects as well as field studies on the use of the extract of mimba leaf to enhance its application to human.